Supporting effects of a N-doped carbon film electrode on an electrodeposited Ni@Ni(OH)2 core–shell nanocatalyst in accelerating electrocatalytic oxidation of oligosaccharides. Issue 22 (9th April 2021) - Shiba, Shunsuke; Ohta, Saki; Ohtani, Kazuya; Takahashi, Shota; Kato, Dai; Niwa, Osamu
Abstract : The supporting effect of a N-doped carbon film induced superior crystallinity in electrodeposited Ni@Ni(OH)2 core–shell nanoparticles. Abstract : The supporting effect of a N-doped carbon film induced superior crystallinity in electrodeposited Ni@Ni(OH)2 core–shell nanoparticles. This improvement resulted in a much higher regeneration rate of catalytic sites (NiOOH), leading to higher oxidation currents of sugars. Also, the overpotential of the maltopentaose (G5) oxidation reaction decreased significantly, probably due to the effect of the electrostatic interaction between NPs and G5.